Comparison of MAUT and EDAS Methods for News Media Selection on Youtube Platform Using ROC Weighting - Rizki Aulia Putra; Dandi Eko Prasetyo; Ahmad Kurniawan; Kahlil Gibran (IJATIS: Indonesian Journal of Applied Technology and Innovation Science, 2025)
News media is one of the things that is considered in getting information. In order to avoid issues or news that are not good, especially those smelling of politics in Indonesia, it is necessary to choose which media can be used as a reference, especially on YouTube as an alternative place to watch and get news. This problem can be solved with the help of a decision support system, which can choose an alternative news media with the help of the MAUT and EDAS methods. The alternatives tested for calculation are obtained based on how often the media is trending on YouTube. In future calculations, based on criteria determined from the results of expert interviews, namely transparency, credibility, news sources and subscribers will be tested to get the best news media with the help of ROC weighting. With the criteria that have been determined and the calculation of the MAUT and EDAS methods, getting the best news media ranking results from both methods is CNN Indonesia with a final value of preference 1. These results will be an illustration for the people of Indonesia in sorting out the news on each news media on YouTube.